2016
DOI: 10.1007/s10792-016-0237-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mean platelet volume and central serous chorioretinopathy

Abstract: The aim of this study was to investigate the mean platelet volume (MPV) of patients with central serous chorioretinopathy (CSCR). Thirty patients were included in the study. Thirty healthy volunteers were recruited as the control group. All patients and control subjects underwent complete ocular examination. Hemoglobin, hematocrit, white blood cell, neutrophil, lymphocyte, platelet count, and MPV of the participants were recorded. Data of patients with CSCR were compared with the control subjects. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The comparison of anti‐CNV effect between bevacizumab and ranibizumab is controversial. Further researches are needed to resolve the contradiction …”
Section: The Drug Treatment Of Cnvmentioning
confidence: 99%
“…The comparison of anti‐CNV effect between bevacizumab and ranibizumab is controversial. Further researches are needed to resolve the contradiction …”
Section: The Drug Treatment Of Cnvmentioning
confidence: 99%
“…Dursun et al assessed MPV in patients with CSCR. 29 Similarly, MPV value was found to be higher in CSCR patients than controls. In that study, CSCR patients were not stratified as acute or chronic.…”
Section: Discussionmentioning
confidence: 90%
“…To the best of our knowledge, in the literature, the only study assessing MPV in patients with CSCR was conducted by Dursun et al 29 However, there is no study assessing MPV and NLR in patients with CSCR in the literature. In this study, it was aimed to evaluate MPV and NLR values and their relationship with clinical findings in patients with CSCR.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Similarly, increased MPV has been seen in patients with ankylosing spondylitis, hip osteoarthritis and central serous chorioretinopathy. [20][21][22] Conversely, lower MPV concentrations have been reported in patients with acute mania, acute pancreatitis and venous thromboembolism. [23][24][25] Moreover, Wang et al reported a relationship between decreased MPV and severe periodontitis, suggesting that MPV may be a useful inflammatory marker reflecting the periodontal disease.…”
Section: Discussionmentioning
confidence: 99%